Treatment differences in IDH–wildtype glioma – the impact of surgery and adjuvant therapy - Keric, Naureen; Krenzlin, Harald; Lange, Felipa; Dauth, Alice; Freyschlag, Christian F.; Schnellg, Oliver; Misch, Martin; von der Brelie, Christian; Gempt, Jens; Krigers, Aleksandrs; Wagner, Arthur; Mielke, Dorothee; et al. (Journal of Neuro-Oncology, 2026)
Background and objectives: Isocitrate dehydrogenase (IDH) wildtype (wt) astrocytomas without the microscopic features of glioblastoma have high recurrence rates and were re-classified in the presence of certain molecular features as CNS WHO grade 4 tumors in the latest WHO classification of 2021. This study examines the clinical heterogeneity within this histologically defined group and explores implications for treatment decisions, with particular focus on the role of surgical resection. Methods: Data acquisition was conducted as a multi-center retrospective analysis at 6 University Hospitals (2016-2019). Patients with IDH-wt diffuse astrocytoma without histological features of glioblastoma were enrolled. Patients presenting with IDH-wt classical glioblastoma from one institution served as controls. Primary outcome parameters were extent of resection (EOR) according to RANO 2.0 criteria, progression-free survival (PFS), and overall survival (OS). Results: 160 patients with IDH-wt astrocytoma (37.5 % females) and 203 patients with IDH-wt glioblastoma (43.8 % females), were enrolled. The median age in patients with astrocytoma was younger (58.1 vs. 67.6 years; p<0.0001). Mean overall survival was significantly longer in astrocytomas (36.1 ±15.1 months) compared to glioblastomas (17.9 ±2.7 months) (p<0.0001). The extent of tumor resection is a significant factor for PFS and OS in both groups. In IDH-wt astrocytoma OS is doubled after resection of more than 50% of radiographic tumor and tripled if resection of >98% is achieved. In IDH-wt glioblastoma, resection of more than 80% of the tumor volume is needed to achieve tripled OS. MGMT methylation was not associated with longer survival in IDH-wt astrocytoma (p=.2124). While concomitant radiochemotherapy (Stupp/CeTeG) was superior to monotherapy in IDH-wt glioblastoma (p=.0094) it is non-superior to sequential therapy (radiotherapy followed by chemotherapy) in IDH-wt astrocytoma (p=.1134). Conclusion: The presented data suggests that the clinical course of IDH-wt astrocytoma, is different from IDH-wt glioblastoma with an early onset and longer survival. As concomitant radiochemotherapy is non-superior in IDH-wt astrocytoma, maximum safe resection is even more important than in classical IDH-wt glioblastoma.
CRIS-Team Scopus Importer:2026-01-16
Keywords: Adjuvant therapy; Astrocytoma; DH1/2; EOR; MGMT; Survival